Recent trends in household wealth in the United States: rising debt and the middle-class squeeze - Edward N. Wolff (Levy Economics Institute of Bard College, 2007)
I find here that the early 2000s witnessed both exploding debt and the middle-class squeeze. While median wealth grew briskly in the late 1990s, it fell slightly between 2001 and 2004, while the inequality of net worth increased slightly. Indebtedness, which fell substantially during the late 1990s, skyrocketed in the early 2000s. Among the middle class, the debt-to-income ratio reached its highest level in 20 years. The concentration of investment-type assets generally remained as high in 2004 as during the previous two decades. The racial and ethnic disparity in wealth holdings, after stabilizing during most of the 1990s, widened in the years between 1998 and 2001, but then narrowed during the early 2000s. Wealth also shifted in relative terms, away from young households (particularly those under age 35) and toward those in the 55-64 age group.
Keywords: D31; J15; 330; Household Wealth; Inequality; Racial Inequality; Portfolio Composition